Using a Modified Postauricular Hemicoronal Incision to Manage Unilateral Zygomaticomaxillary Complex Fracture. Issue 8 (November 2019) - Liu, Min; Lv, Kun; Li, Zubing; Yang, Xuewen
Abstract : Background: The surgical approach of the zygomaticomaxillary complex fracture is usually performed with preauricular coronal incision assisted with intraoral maxillary sulcus incision. There will be preauricular scars postoperatively. Methods: The authors introduce a postauricular hemicoronal incision to avoid the formation of scars in front of the ear. Results and Discussion: The postauricular hemicoronal incision can avoid vascular damage caused by careless operation in the preauricular approach. It eliminates the possibility of dissection or ligation of the superficial arteries and veins when preauricular approach was used. It results in no scar in front of ear, while reducing suture time and complexity.